2015
DOI: 10.1136/bmjopen-2015-008682
|View full text |Cite
|
Sign up to set email alerts
|

Human trafficking and health: a cross-sectional survey of NHS professionals’ contact with victims of human trafficking

Abstract: Objectives(1) To estimate the proportion of National Health Service (NHS) professionals who have come into contact with trafficked people and (2) to measure NHS professionals’ knowledge and confidence to respond to human trafficking.DesignA cross-sectional survey.SettingFace-to-face mandatory child protection and/or vulnerable adults training sessions at 10 secondary healthcare provider organisations in England, and meetings of the UK College of Emergency Medicine.Participants782/892 (84.4%) NHS professionals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 8 publications
1
115
0
Order By: Relevance
“…As others have suggested, contact with the healthcare system may be the only point of contact with a potential source of help that many trafficked individuals have (Sabella, 2011). However, because only a small proportion of US and UK based healthcare professionals (Chisolm-Straker et al, 2012) (Ross et al, 2015), have ever received any training in human trafficking, much more could be done to prepare the healthcare system to assist with human trafficking intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As others have suggested, contact with the healthcare system may be the only point of contact with a potential source of help that many trafficked individuals have (Sabella, 2011). However, because only a small proportion of US and UK based healthcare professionals (Chisolm-Straker et al, 2012) (Ross et al, 2015), have ever received any training in human trafficking, much more could be done to prepare the healthcare system to assist with human trafficking intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A similar U.K.-based study surveyed 782 healthcare professionals and found that 20% had received any training on human trafficking (Ross et al, 2015). Perpetrators may present as caring, well-spoken family members or romantic partners when they accompany their victims to healthcare settings, making identification of victims by healthcare professionals that much more challenging (Becker & Bechtel, 2015).…”
Section: The Healthcare Setting: a New Venue For Identifying Victims mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to enduring abortions and miscarriages with little, if any, clinical attention, trafficking survivors might not have adequate access to prenatal health care and can suffer from pregnancy-complicating sexually transmitted infections, such as HIV [8,10]. Not surprisingly, a study from the United Kingdom showed that the health professional group most likely to encounter trafficked persons is maternity services professionals [11]. And a US-based study of trafficked persons found that approximately one quarter of labor and sex trafficked persons reported that they saw obstetricians during their period of exploitation [12].…”
Section: Health Implications Of Being Traffickedmentioning
confidence: 99%
“…This is particularly true for patients who are being trafficked or are incarcerated or in police custody. [42][43][44] Shared decision making in the ED setting among patients with socioeconomic challenges may be inhibited by a perceived power differential between physicians and their patients, beyond that experienced by more affluent patients. While many patients are able to articulate their view of healthcare as a service, the impact of a perceived inherent power differential may manifest in various modes of patient behavior that create significant barriers to effective communication with the ultimate outcome of decreased participation by the patient in SDM.…”
Section: Socioeconomic Disadvantagementioning
confidence: 99%